PENGARUH MOTIVASI ORANG TUA TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DAN BUDI PEKERTI KELAS VIII A SMP NEGERI 2 GUNUNG TOAR - Vivi Nesti; Sopiantun Nahwiyah; Alhairi Alhairi (Universitas Islam Kuantan Singingi, 2023)
Motivation is the process of generating, maintaining and controlling interests. The motivation consists of internal and external, internal motivation is motivation that comes from within oneself, while external motivation is the driving force that comes from outside one's self. One form of external motivation is parental motivation. Parents' motivation is an effort to encourage their children to be more enthusiastic in learning by giving rewards if they excel.Based on the results of the author's observations and interviews with parents of class VIII A SMP N 2 Gunung Toar, there is still a lack of parental attention and motivation for their children at home, lack of awareness from within students to learn because they are not good at adapting to technological advances.The purpose of this study was to determine whether there was an influence of parental motivation on the learning outcomes of class VIII A students of SMP N 2 Gunung Toar.The research methodology consists of the location of this research in SMP N 2 Gunung Toar, Gunung Toar District, Kuantan Singingi Regency. The subjects of this study were all parents of 19th grade students of SMP N 2 Gunung Toar. The object of this research is the influence of parents' motivation on learning outcomes in the subjects of Islamic Religious Education and Budi Pekerti. Data collection techniques are observation, interviews, questionnaires and documentation